LOCAL POLITICAL DYNAMICS IN EMPOWERING PKK AND PREVENTING NARCOTICS AMONG YOUTH: AN ANALYSIS OF THE COMMUNITY SERVICE (KKN) PROGRAM OF UINSU MEDAN IN SERAPIT VILLAGE - Khoirul Huda; Azmi alfaiz nur; ismi aulia palem; Annisa Ramayani; Muhammad ridholi (PERSPEKTIF: Journal of Social and Library Science, 2025)
This study analyzes the influence of local political dynamics on the empowerment of the Family Welfare Development program (PKK) and its role in preventing narcotics abuse in Serapit Village, Langkat Regency. The purpose of the research is to identify the relationship between village politics, community participation, and the effectiveness of community-based social programs. The study employs a descriptive qualitative approach, using primary data obtained through observation, interviews, and documentation during the KKN program of UIN Sumatera Utara. The findings show that participatory political support strengthens PKK empowerment and increases community awareness of the dangers of narcotics. Collaboration among university students, PKK members, and village authorities creates an effective and sustainable model of social empowerment. The study concludes that local politics can serve as an instrument of social transformation when managed inclusively and grounded in community collaboration.